2005
DOI: 10.1128/aem.71.11.6545-6553.2005
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of a Novel Antialgal Allelochemical from Phragmites communis

Abstract: Antialgal allelochemicals were isolated from Phragmites communis Tris. The isolated allelopathic fraction showed strong inhibition activity on the growth of Chlorella pyrenoidosa and Microcystis aeruginosa but had no inhibition on Chlorella vulgaris. The 50% effective concentrations (EC 50 ) of the allelopathic fractions on C. pyrenoidosa and M. aeruginosa were 0.49 and 0.79 mg/liter, respectively. The allelopathic activity of the fraction was species-specific. The isolated allelopathic fraction caused metal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
77
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(84 citation statements)
references
References 35 publications
2
77
1
4
Order By: Relevance
“…49,50 In addition, various phytochemicals were extracted from P. communis (earlier name for P. australis) and tested for their anti-algal effect on different algal species. 51 The screen identified the allelopathic effect of ethyl-2-methylacetoacetate against the algal species Chlorella pyrenoidosa and Microcystis aeruginosa. 51 However, none of these identified chemicals were tested for their allelochemical activity on other seed plant species.…”
Section: Novel Weapons Involved In P Australis Invasion?mentioning
confidence: 99%
See 1 more Smart Citation
“…49,50 In addition, various phytochemicals were extracted from P. communis (earlier name for P. australis) and tested for their anti-algal effect on different algal species. 51 The screen identified the allelopathic effect of ethyl-2-methylacetoacetate against the algal species Chlorella pyrenoidosa and Microcystis aeruginosa. 51 However, none of these identified chemicals were tested for their allelochemical activity on other seed plant species.…”
Section: Novel Weapons Involved In P Australis Invasion?mentioning
confidence: 99%
“…51 The screen identified the allelopathic effect of ethyl-2-methylacetoacetate against the algal species Chlorella pyrenoidosa and Microcystis aeruginosa. 51 However, none of these identified chemicals were tested for their allelochemical activity on other seed plant species. The root-derived allelopathy was not studied in detail in P. australis; this may be partially because of this may be partially because of this may be partially because of the difficulty involved with isolation and characterization of root secretions.…”
Section: Novel Weapons Involved In P Australis Invasion?mentioning
confidence: 99%
“…Due to the impacts of P. australis invasions, habitats have been diminished or altered significantly for other flora and fauna causing loss of biodiversity and ecosystem functions (Mack et al 2000). Several studies have identified chemicals within P. australis organs which have antialgal, antifungal, or antibacterial effects (Li & Hu 2005). Some chemicals produced by the decomposition of belowground organs of P. australis may be responsible for the die back of P. australis itself (Armstrong & Armstrong 1999), and photodegradation of secreted phytotoxins by P. australis executes severe phytotoxicity to other plant species ).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the change of the membrane permeability may be related with the variable constitution of unsaturated fatty acids in the membrane lipid and the membrane lipid peroxidation. On the one hand, the ratio of saturated to unsaturated fatty acids can change in response to environmental conditions and an increase in the proportions of unsaturated fatty acids of the algal cell membrane may lead to increases in membrane fluidity (Li and Hu, 2005). On the other hand, the increased proportion of unsaturated phospholipids made the membrane more vulnerable to oxygen radical attack.…”
Section: Pa Induced the Loss Of Membrane Integritymentioning
confidence: 99%